Statutes of Ohio and of the Northwest territory 1740, ch. 834, § 6 (Vol. 3, 1835). - (:unkn) unknown (General Publisher, 1831)
That if any person or persons shall play bullets along or across any street in any town or village within this state; or if any person or persons shall run any horse or horses within the limits of any such town or village; or if any person or persons shall shoot or fire a gun at a target within the limits of any recorded town plat in this state: every person or persons so offending shall be fined in a sum not exceeding five dollars, nor less than fifty cents."
--
Keywords: DISCHARGE